ARTISTIC DISCOURSE AND ANTONYMS IN IT AS A CULTURAL FACTOR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article is discussed about artistic discourse and antonyms. Language and speech are closely related. Language is a complex of units built on the basis of words and grammatical principles that change over time, and speech is the manifestation of language in expression, thought, emotion and action in a certain national language. Speech features depend on its purpose and content. In this regard, the characteristic of artistic discourse is that it is considered a form of figurative form. Because of this, it has the characteristics common to all forms in art, such as imagery and expressiveness (emotional coloring).